Comparison of Auditory Steady-State Responses With Conventional Audiometry in Older Adults - Tarawneh, Hadeel Y.; Sohrabi, Hamid R.; Mulders, Wilhelmina H. A. M.; Martins, Ralph N.; Jayakody, Dona M. P. (Frontiers in Neurology, 2022)
Behavioural measures, such as pure-tone audiometry (PTA), are commonly used to determine hearing thresholds, however, PTA does not always provide reliable hearing information in difficult to test individuals. Therefore, objective measures of hearing sensitivity that require little-to-no active participation from an individual are needed to facilitate the detection and treatment of hearing loss in difficult to test people. Investigation of the reliability of the auditory steady-state response (ASSR) for measuring hearing thresholds in older adults is limited. This study aimed to investigate if ASSR can be a reliable, objective measure of frequency specific hearing thresholds in older adults. Hearing thresholds were tested at 500Hz, 1000Hz, 2000Hz, and 4000Hz in 50 participants aged between 60 and 85 years old, using automated PTA and ASSR. Hearing thresholds obtained from PTA and ASSR were found to be significantly correlated (p<.001) in a cohort consisting of participants with normal hearing or mild hearing loss. ASSR thresholds were significantly higher as compared to PTA thresholds, but for the majority of cases the difference remained within the clinically acceptable range (15dB). This study provides some evidence to suggest that ASSR can be a valuable tool for estimating objective frequency-specific hearing thresholds in older adults and indicate that ASSR could be useful in creating hearing treatment plans for older adults who are unable to complete behavioural PTA. Further research on older adults is required to improve the methodological features of ASSR to increase consistency and reliability, as well as minimise some of the limitations associated with this technique.